Interprofessional School Team Members" Views on the School Nurse Role: A Cross-Sectional Study - Theodoula Adamakidou; Chrysoula Tsiou; Sotirios Plakas; Paraskevi Boutsoli; Irene Palatza; Olympia Konstantakopoulou; Marianna Mantzorou and Alexandra Mantoudi (International Journal of Caring Sciences, 2024)
Interprofessional School Team Members" Views on the School Nurse Role: A Cross-Sectional Study